PENGENALAN METODE VAMELA THE ANESTHESIA (HYPNOSIS ANESTHESIA METHOD VACCINE) SEBAGAI ALTERNATIF ANESTESI YANG AMAN DAN EFEKTIF - Syaeful Islam (Najah: Journal of Research and Community Service, 2023)
Hypnotherapy or clinical hypnosis is a mind therapy and healing technique that useshypnosis methods to give positive suggestions or commands to the subconscious mind to curea psychological disorder or to change thoughts, feelings and behavior for the better. Hypnosisis not like other ways of treating the symptoms or effects that appear. By eliminating the cause,the consequences will automatically disappear or be cured (Ratna, 2017). Case in point, forexample, treatment of anxiety. Anxiety that occurs without any external reason and begins toaffect human daily functioning, mental health professionals view it as a psychological problemcalled anxiety disorder.Previously, in the working area of the Pajarakan Health Center, many patients, rangingfrom children, adolescents, adults and even the elderly, were afraid of needles during the Covid-19 vaccination activities or complete basic immunization. Then the Pajarakan Health Centerbegan to take action and began to collect data to carry out problem-solving analysis also throughcoordination efforts with cross-programs and cross-sectors so that an activity "Vaccination withanesthesia hypnosis method" emerged which was pioneered by one of the Pajarakan HealthCenter employees, namely Ns. Syaeful Islam S.Kep. Then the vaccination with the hypnosisanesthesia method was also launched at the birthday of the Indonesian National NursesAssociation which was attended by the Probolinggo regent, the police chief, the head of thehealth office, the police chief, and other OPDs in the Probolinggo district work area.With the basic vaccination/immunization complete with the anesthetic hypnosismethod, it is hoped that the handling of vaccine patients in the working area of the PajarakanHealth Center will achieve the expected target indicators. So with a quick response to provideinformation that in the Pajarakan Health Center there is a hypnosis method vaccine that canincrease comfort, security in the working area of the Pajarakan Health Center in particular.